The Success of Syirkah MSMEs: Literacy, Trust, ICG, and Fintech - Handoko, Dodi Okri; Siregar, Saparuddin; Marliyah; Zulhelmy (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2025)
Purpose - This study aims to analyze the determinants of direct shirkah success in MSMEs in Pekanbaru using a mixed-methods approach. Method - In-depth interviews were conducted with 10 key informants, followed by a survey of 200 respondents. Quantitative analysis using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4. Findings - The results show that Islamic financial literacy and trust have a significant effect on Islamic Corporate Governance (ICG). Furthermore, ICG plays a crucial role in enhancing business performance and sustainability. Islamic fintech has been proven to mediate the influence of literacy on sustainability, while ICG moderates the relationship between risk management and business sustainability. Regulatory support has no significant effect on ICG, indicating a policy gap. Implications - This research contributes to the Islamic finance literature by integrating aspects of literacy, social capital, Islamic governance, financial technology, and spiritual capital. The practical implications are intended for MSMEs, regulators, and Islamic financial institutions to strengthen literacy, clarify contracts, and optimize the use of Islamic fintech.